Contribution of Arm Muscle Strength and Hand Eye Coordination to the Lower Service Results of the Mts S Muaro Sijunjung Volleyball Extracurricular Team - Hudi Setiawan; M. Fransazeli Makorohim (Eduvest - Journal of Universal Studies, 2024)
The aim of this research was to see the contribution of arm muscle strength, hand eye coordination to the volleyball bottom serve results of the MTs S Muaro Sijunjung Volleyball extracurricular team. The type of research used in this research is correlation research. The population in this study were all volleyball extracurricular athletes at MTs S Muaro Sijunjung, while the sampling technique in this study used total sampling, so the sample in this study was 18 people. The tests used in this research used arm muscle strength tests (push ups), baseball throwing and catching, and volleyball bottom serve tests. From the results of tests carried out on MTs S Muaro Sijunjung volleyball extracurricular athletes, the results obtained were that there was a contribution between arm muscle strength to the lower serve of 1.23% and the remaining 98.77% was influenced by other factors, there was a contribution between hand eye coordination and volleyball bottom serve is 8.26% and the remaining 91.74% is influenced by other factors, and there is a contribution of arm muscle strength and hand eye coordination to volleyball bottom serve of 2.97% and the remaining 97.03% is influenced by other factors.